Stock market synchronization: The role of geopolitical risk - Kazi Sohag; Rogneda Vasilyeva; Alina Urazbaeva; Valentin Voytenkov (Journal of Risk and Financial Management, 2022)
Given the importance of stock market synchronization for international portfolio diversification, we estimate the degrees of co-movements among US, Chinese and Russian markets. By applying the TVP-VAR approach, we measure total and bivariate synchronization indices utilizing daily data from 1998 to 2021. Our analysis demonstrates that the total connectedness index (TCI) is 26.15% among the three markets. We find that the US market is the highest volatility contributor, whereas the Russian market is the highest receiver. Since stock market synchronization is exposed to geopolitical risk, at the second stage, we apply the Quantile-on-Quantile framework to measure the response of total and bilateral connectedness indices to geopolitical risk (GPR). The findings affirm our proposition that GPR impedes TCI when it has a bullish state and a higher quantile of GPR. The response of bilateral connectedness is negative towards GPR concerning US-China and US-Russian pairs. However, the degree of connectedness between Russian and Chinese stock markets is less responsive to GPR.
Keywords: 650; geopolitical risk; Quantile-on-Quantile; stock market synchronization; TVP-VAR